No association between perinatal mood disorders and hypertensive pregnancies - Araji, Sarah; Griffin, Ashley; Kassahun-Yimer, Wondwosen; Dixon, Laura; Spencer, Shauna-Kay; Belk, Sheila; Ohaegbulam, Gail; Wallace, Kedra (Frontiers in Psychiatry, 2022)
Mental health disorders such as anxiety and /or depression are the most common mental health disorders seen among reproductive aged women and can increase during pregnancy. Many sociodemographic risk factors have been associated with anxiety and/or depression in pregnancy, which can lead to adverse maternal and infant outcomes including the risk of a hypertensive pregnancy. The current study prospectively examined self-reported anxiety, depression and stress in pregnant women without a history of fetal loss or mood disorders beginning at 20-26 weeks. At each study visit, circulating immune factors associated with perinatal mood disorders were measured in blood samples that were collected. A total of 65 women were eligible for data analysis, 26 of which had hypertensive pregnancies. There was not a significant difference in self-reported depression, anxiety or stress between hypertensive disorders of pregnancy and normotensive women. Black women were more likely to have a hypertensive pregnancy and develop a perinatal mood disorder compared to non-black women. Both the inflammatory cytokines interleukin-17 and tumor necrosis factor-alpha were increased in patients with perinatal mood disorders. However, additional research is needed in a larger sample to truly understand the relationship between these factors along with the underlying etiologies and the associated outcomes.